(untitled) (American Journal of Islam and Society, 2010)
This book treats the debate among Muslims over the authority of hadith, which by the ninth century had been raised to the level of scripture. The author’s main purpose is to show that modern Muslim thinkers who question its status as a source of law are not the first ones to do so and thus cannot be dismissed as inauthentic aberrations or the results of a western, colonialist plot to undermine Islam. In addition, modern arguments against this view have close parallels in the opinions attributed to those of their predecessors. Hadith as Scripture thus has a strong presentist concern, despite its treatment of classical Islamic sources, and can be seen as apologetic in that it seeks to defend the Qur’an-only position from unfair detraction ...